PROFESSIONAL AND PERSONAL SELF-DEVELOPMENT OF FUTURE ENGINEERS IN EDUCATIONAL PROCESS: NATURE AND MECHANISMS - Mykhaylychenko, Valentina; Hura, Tetiana; Galushchak, Irina (PSYCHOLOGICAL JOURNAL, 2020)
The article indicates the orientation of the educational process of institutions of higher education on the student’s professional and personal self-development, which provides for the creation of such a development environment that would make the student himself more consciously and purposefully master the methodology and technology of self-knowledge, self-education, self-training and self-improvement. The personal result of professional self-development is manifested in the dynamics of the image of self and its characteristics. In order for the process of professional and personal self-development to proceed efficiently, a person, first of all, must have a high level of preparedness for its implementation. Therefore, the article examines the state of the problem of its formation in the process of professional training of future professionals in institutions of higher education, namely, at a technical university .. The article considers the essence of professional-personal self-development and explains the content of its mechanisms, as well as the need to form students' preparedness for it in the studying process in institutions of higher education. Its main mechanisms as a targeted influence of a person on himself are self-knowledge, self-determination, self-control, self-regulation, self-education and independent study work. The article describes the pedagogical experiment to identify the preparedness of future managers for professional and personal self-development was conducted at the National Technical University "Kharkov Polytechnic University", in which 86 first-year students of the Chemical Engineering Institute took part. Homogeneous study groups were selected, from which the experimental and control groups of participants were formed. Students of both groups have approximately the same results. The results of the first stage of the pedagogical experiment on the formation of preparedness for professional and personal self-development are presented. The purpose of the experiment was to ensure that students recognize the need and importance of professional and personal self-development in the process of acquiring fundamental and special knowledge, skills for the successful implementation of professional activities, the need and feasibility of introspection and self-knowledge and other mechanisms of self-development, learn to formulate goals and objectives, plan their actions and interaction with participants in the educational process. A higher level of students of the experimental group was noted. It is a result of their focused independent study work and pedagogical and psychological support by the teachers of the department. The article draws attention to the low psychological preparedness of future engineers and the insufficient development of innovative pedagogical technologies that contribute to the formation of students' preparedness for professional and personal self-development . Based on the study, the authors made the following conclusions: The formation in students of a dominant attitude-motivation for self-education and self-training, understanding the need for continuous self-development throughout life will help to solve many of today's problems of education. Having acquired certain experience and qualities in the process of activity, a person starts on this basis to choose goals and methods of activity freely and independently, manage his actions, and at the same time improve and develop his abilities to carry out these activities, changing and educating himself. Without a deep understanding of oneself, one’s orientation, and without an adequate assessment of one’s abilities, neither clarity of a professional goal, nor firmness and consistency in achieving it are possible. The lack of formation of a attitude to oneself as a future specialist hinders the process of professional and personal self-development, because students understands the contradction betweeb their qualities and the requirements of the profession and the social and moral requirements of society by means of self-awareness. As a result they internally encourages themselves to overcome this contradictions, forming a preparedness to self-development. The goal or requirement imposed by other people can become personal for the students if they contribute to the satisfaction of their specific needs or they a stage or a way of satisfying them. In this case, the student no longer acts as a passive performer, but as an active participant, which contributes to a greater involvement of the student in the activity. The transformation of external requirements into individual goals is one of the principles of a personality-oriented approach to learning The authors consider the prospects of further research the development of the most favorable conditions for stimulating the development and self-development of needs, interests, intentions in the process of training future engineers.